2016
DOI: 10.1007/s11356-016-6260-x
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of six fungicides in greenhouse-grown tomatoes with processing and health risk

Abstract: Greenhouse studies were conducted to evaluate the dissipation rate kinetics and estimate the behavior of selected pesticides after washing, peeling, simmering, and canning of tomato expressed as processing factor (PF). Two varieties (Marissa and Harzfeuer) were treated by six fungicides: azoxystrobin, boscalid, chlorothalonil, cyprodinil, fludioxonil, and pyraclostrobin at single and double dose and risk assessment defined as hazard quotient was performed. The QuEChERS method was used for sample preparation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 30 publications
(34 reference statements)
3
47
1
Order By: Relevance
“…Different processing methods have different effects on agricultural pesticides . The processing factor (PF), defined as ratio of pesticide residues in processed products and the primary agricultural pesticide residue levels or the raw material pesticide residue levels, is used to evaluate the variety and redistribution of pesticide residues during the food‐processing procedure . A PF > 1 means that the residual levels increased during processing while PF < 1 means that residual levels decreased during processing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different processing methods have different effects on agricultural pesticides . The processing factor (PF), defined as ratio of pesticide residues in processed products and the primary agricultural pesticide residue levels or the raw material pesticide residue levels, is used to evaluate the variety and redistribution of pesticide residues during the food‐processing procedure . A PF > 1 means that the residual levels increased during processing while PF < 1 means that residual levels decreased during processing.…”
Section: Resultsmentioning
confidence: 99%
“…46 The processing factor (PF), defined as ratio of pesticide residues in processed products and the primary agricultural pesticide residue levels or the raw material pesticide residue levels, is used to evaluate the variety and redistribution of pesticide residues during the food-processing procedure. [47][48][49] A PF > 1 means that the residual levels increased during processing while PF < 1 means that residual levels decreased during processing. Table 7 presents the redistribution of triadimenol residues from rapeseed to rapeseed oil and processing factors (PFs) using the cold-press or hot-press technique.…”
Section: Processing Factorsmentioning
confidence: 99%
“…The results showed that boscalid dissipation pattern followed the first-order kinetics with the half-lives of 4.9 and 6.4 days, respectively. The studies conducted by Jankowska et al (2016) showed that the dissipation time for boscalid in tomatoes is 2.88 days for Marissa variety and 3.09 days for Harzfeuer variety. For the pyraclostrobin the dissipation time is 2.70 and 2.78 days for Marissa and Harzfeuer varieties, respectively.…”
Section: Boscalid and Pyraclostrobin Residuesmentioning
confidence: 99%
“…Fungicides in plants are essential for inhibiting or reducing disease development by damaging pathogen cell membranes , and have been widely used to protect plants during growth modulation processes. However, residual fungicides can enter plants by diverse modes of action and then bioaccumulate in other organisms, making them a serious threat to human health . To guarantee food security, the detection of these residues in food has received increasing attention, and the European Commission has set some maximum residue limits (MRLs) to guarantee consumer safety .…”
Section: Introductionmentioning
confidence: 99%
“…Fungicides in plants are essential for inhibiting or reducing disease development by damaging pathogen cell membranes [1], and have been widely used to protect plants during growth modulation processes. However, residual fungicides can enter plants by diverse modes of action and then bioaccumulate in other organisms, making them a serious threat Abbreviations: EA-DSPE, effervescence-assisted dispersive solid-phase extraction; MRL, maximum residue limit; DLLME, liquid-liquid microextraction; ATP, attapulgite; ␤-CD, ␤cyclodextrin; M-␤-CD/ATP, ␤-cyclodextrin/attapulgite; IL, ionic liquid; IL-M-␤-CD/ATP, ionic-liquid-modified magnetic ␤-cyclodextrin/attapulgite; OFAT, one-factor-at-a-time; DAD, diode array detection; EF, enrichment factor; R 2 , correlation coefficient to human health [2,3]. To guarantee food security, the detection of these residues in food has received increasing attention, and the European Commission has set some maximum residue limits (MRLs) to guarantee consumer safety [4].…”
Section: Introductionmentioning
confidence: 99%